Registration of 'Puma' Soft White Winter Wheat. Issue 3 (18th July 2014) - Carter, A. H.; Jones, S. S.; Cai, X.; Lyon, S. R.; Balow, K. A.; Shelton, G. B.; Higginbotham, R. W.; Chen, X. M.; Engle, D. A.; Baik, B.; Guy, S. O.; Murray, T. D.; et al.
Abstract : Resistance to strawbreaker foot rot (caused by Oculimacula yallundae Crous & W. Gams and O. acuformis Crous & W. Gams), stripe rust (caused by Puccinia striiformis Westend. f. sp. tritici Eriks.), and Cephalosporium stripe (caused by Cephalosporium gramineum Nisikado and Ikata) are important traits for winter wheat ( Triticum aestivum L.) cultivars produced in the Pacific Northwest region of the United States. The objective of this research was to develop an adapted winter wheat cultivar with effective resistance to these diseases. 'Puma' (Reg. No. CV‐1097, PI 670038) soft white winter wheat ( Triticum aestivum L.) was developed and released in August 2013 by the Agricultural Research Center of Washington State University. Puma was tested under the experimental designations 5J030731, 5J030731–2, and WA008134, which were assigned through progressive generations of advancement. Puma is a semidwarf cultivar adapted to intermediate to high rainfall (>400 mm of average annual precipitation), unirrigated wheat production regions of Washington. Puma is resistant to strawbreaker foot rot, has high‐temperature, adult‐plant resistance to the stripe rust pathogen, is tolerant to Cephalosporium stripe, is intermediate in height, has midseason maturity, and has a high test weight and grain yield potential. Puma has end‐use quality properties similar or superior to those of 'Stephens', 'Brundage 96', and 'Xerpha'.